Smiling down the line : info-service work in the global economy - Russell, Bob, 1950- (Studies in comparative political economy and public policy., 2009)
Smiling Down the Line theorizes call centre work as info-service employment and looks at the effects of ever-changing technologies on service work, its associated skills, and the ways in which it is managed.